2017
DOI: 10.1007/s10103-017-2413-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pulsed dye laser treatment for common warts is not influenced by the causative HPV type: a prospective study

Abstract: Verruca vulgaris (VV) is a prevalent skin condition caused by various subtypes of human papilloma virus (HPV). The most common causes of non-genital lesions are HPV types 2 and 4, and to a lesser extent types 1, 3, 26, 29, and 57. Although numerous therapeutic modalities exist, none is universally effective or without adverse events (AE). Pulsed dye laser (PDL) is a favorable option due to its observed efficacy and relatively low AE rate. However, it is not known which verrucae are most likely to respond to PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Whereas topical retinoids are administered in milder cases, systemic retinoids are usually reserved for more widespread and/or recalcitrant CVW, as in the case of immunosuppressed patients. These patients tend to have multiple, hypertrophic, treatment resistant CVW, and according to our experience, best respond to the combination of systemic retinoids and laser treatment 9 …”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Whereas topical retinoids are administered in milder cases, systemic retinoids are usually reserved for more widespread and/or recalcitrant CVW, as in the case of immunosuppressed patients. These patients tend to have multiple, hypertrophic, treatment resistant CVW, and according to our experience, best respond to the combination of systemic retinoids and laser treatment 9 …”
Section: Discussionmentioning
confidence: 78%
“…These patients tend to have multiple, hypertrophic, treatment resistant CVW, and according to our experience, best respond to the combination of systemic retinoids and laser treatment. 9 Among the types of systemic retinoids used, oral etretinate 1 mg/ kg/day was the most effective, with a CR rate of 75% and no cases of relapse during a follow-up period of nearly 2 years. However, it was evaluated in only one prospective cohort study, so the results should be viewed with caution.…”
Section: Systemic Retinoidsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, in other studies there was no correlation between location of lesions and response rates 6,16,17 . Two studies reported no significant correlation between type of HPV and clearance rate 10,11 …”
Section: Methodsmentioning
confidence: 94%
“…El período de recuperación es rápido. 27 Los regímenes recomendados por la CDC para condilomas en el meato urinario son crioterapia o cirugía, y para lesiones intra-anales se recomienda crioterapia, cirugía o solución de ácido tricloroacético o bicloroacético al 80-90%. 3 Existe una tendencia creciente de utilizar terapia combinada para tratar las verrugas por VPH, denominada "terapia secuencial proactiva" (PST, por sus siglas en inglés), que promete ser un método efectivo para reducir la tasa de recurrencia de las lesiones y evitar la transmisión sexual.…”
Section: Láserunclassified